Fetal muscle extract improves muscle function and performance in aged mice - Jessica Lo, Hiu Tung; Yiu, Tsz Lam; Wang, Yujia; Feng, Lu; Li, Gang; Lui, May Pui-Man; Lee, Wayne Yuk-Wai (Frontiers in Physiology, 2022)
Background Loss of skeletal muscle mass and function is one of the major musculoskeletal health problems in aging population. Recent studies demonstrated differential proteomic profiles at different fetal stages might be associated with muscle growth and development. We hypothesized extract derived from fetal muscle tissues at stage of hypertrophy could ameliorate the loss of muscle mass and strength in aged mice. Methods Skeletal muscle extract from fetal sheep at week16 of gestation and maternal tissue were used in the present study. iTRAQ and KEGG pathway analyses identified DEPs in FSME Vs ASME. Effects of FSME and ASME on human myoblast proliferation were performed. To examine the effect of FSME in vivo, C57BL/6 male mice at 20-month-old were subjected to intramuscular administration of FSME or vehicle control for eight weeks. Grip strength test and ex vivo muscle force-frequency test were performed. Serum samples were collected for determining potential changes in immunological cytokines upon FSME injection. Results Compared with ASME, 697 and 412 peptides were upregulated and downregulated respectively in FSME as indicated by iTRAQ analysis. These peptides were highly related to muscle development, function and differentiation from GO enrichment analysis. FSME promoted cell proliferation of myoblast cells(+300%,p<0.01) without causing significant cytotoxicity at the tested concentration range. After 8 weeks of FSME treatment, the percentage of lean mass(+10%,p<0.05), grip strength(+50%,p<0.01), and ability in fatigue resistance were significantly higher. Isometric force stimulated by different frequencies were higher in control group. Histologically, the control group showed larger cross-sectional area(+20%,p<0.01) while muscle fiber type switch from type IIa to type I was observed in FSME group. Multiplex assay indicated that FSME treatment did not lead to elevated circulatory level of inflammatory cytokines. After treatment, we observed significant drop in the circulating level of IL-12(p40) from 90.8±48.3pg/ml to 82.65±4.4pg/ml, G-CSF from 23476±8341.9pg/ml to 28.35±24.2pg/ml, KC from 97.09±21.2pg/ml to 29.2±7.2pg/ml and RANTES from 325.4±17.3pg/ml to 49.96±32.1pg/ml. Conclusions This is the first study demonstrating the beneficial effect of fetal muscle extract on muscle health in aged mice. Further analysis on the active ingredients of the extract will shed light on the development of a novel treatment for sarcopenia.